Kako smo dobili slovenski TV dnevnik - Prpič, Marko (Javnost (Ljubljana), 2008)
Televizija Ljubljana (now Televizija Slovenija) has been broadcasting its daily news programme, TV dnevnik, since April 15, 1968. For almost thirty years, it had no real competitor in Slovenia. TV Dnevnik determined the daily routine of the majority of viewers. Today it is taken for granted that we have the news programme in our national language, but in 1968 the situation was different, and TV Slovenija achieved this "right" only after a decade-long struggle. In 1958, the Yugoslav television network was established as a result of joint efforts by Studio Ljubljana, Studio Zagreb and Studio Belgrade.Since then, the news programme broadcast across former Yugoslavia was produced by Studio Belgrade, whose privileged position could be partly explained by the most suitable working conditions, its proximity to federal institutions, the best connections with all Yugoslav republics and foreign countries, and above all, by the wish on the part of federal political bodies to control and influence programming content. The decision of Slovenian television to launch its own news programme represented a break with this policy, with other national televisions soon following suit. The article describes the birth of TV Dnevnik as reconstructed from internal documents of RTV Slovenia, press articles and other sources.
Keywords: Jugoslavija; Yugoslavia; Slovenia; Slovenija; mass media; množični mediji; television; televizija; 1958/1968; obveščanje; informiranje; informativne oddaje; slovenščina; Slovene